Existence and stability of forced waves for p-Laplace equations in a shifting habitat - Tianyuan Xu; Gege Liu; Jingxue Yin (Electronic Journal of Differential Equations)
This article concerns the existence and stability of forced waves for p-Laplace equations with a shifting habitat given by a non-decreasing function with a sign change. The existence of forced waves is studied by the monotone iteration method combined with a pair of delicate super- and sub-solutions. Finally, we develop an approximating weighted energy method to prove the $L^p$ stability and exponential convergence of forced waves.